Mitral Regurgitation: Anatomy, Physiology, and Pathophysiology—Lessons Learned From Surgery and Cardiac Imaging - Topilsky, Yan (Frontiers in Cardiovascular Medicine, 2020)
The normal mitral valve apparatus is a dynamic 3-dimensional (3D) system that allows blood to flow from the left atrial (LA) to left ventricular (LV) during diastole and sealing of the LA from the LV during systole. The main components of the mitral apparatus are the mitral annulus (MA), the mitral leaflets, the chordae tendineae, and the papillary muscles (PM) (Fig. 1). Proper valve function is dependent on the integrity and normal interplay of these components. Any imbalance can result in mitral regurgitation (MR), stenosis, or combined dysfunction. Understanding the anatomy and physiology of the mitral valve apparatus is important for the diagnosis, and for comprehending the rationale for repair strategies. In this review we will focus first on normal anatomy and physiology of the different parts of the mitral valve apparatus (MA, leaflets, chordae tendineae and PM). In the second part we will focus on the pathologic anatomic and physiologic derangements associated with different types of MR.